Influence of Platelet Lysate on 2D and 3D Amniotic Mesenchymal Stem Cell Cultures - Pasztorek, Markus; Rossmanith, Eva; Mayr, Christoph; Hauser, Fabian; Jacak, Jaroslaw; Ebner, Andreas; Weber, Viktoria; Fischer, Michael B. (Frontiers in Bioengineering and Biotechnology, 2019)
The mechanobiological behavior of mesenchymal stem cells (MSCs) in two- (2D) or three-dimensional (3D) cultures relies on the formation of actin filaments which occur as stress fibers and depends on mitochondrial dynamics involving vimentin intermediate filaments. Here we investigate whether human platelet lysate (HPL), that can potentially replace fetal bovine serum for clinical-scale expansion of functional cells, can modulate the stress fiber formation, alter mitochondrial morphology, change membrane elasticity and modulate immune regulatory molecules IDO and GARP in amnion derived MSCs. We can provide evidence that culture supplementation with HPL led to a reduction of stress fiber formation in 2D cultured MSCs compared to a conventional growth medium (MSCGM). 3D MSC cultures, in contrast, showed decreased actin concentrations independent of HPL supplementation. When stress fibers were further segregated by their binding to focal adhesions, a reduction in ventral stress fibers was observed in response to HPL in 2D cultured MSCs, while the length of the individual ventral stress fibers increased. Dorsal stress fibers or transverse arcs were not affected. Interestingly, ventral stress fiber formation did not correlate with membrane elasticity. 2D cultured MSCs did not show differences in the Young’s modulus when propagated in the presence of HPL and further cultivation to passage 3 also had no effect on membrane elasticity. In addition, HPL reduced the mitochondrial mass of 2D cultured MSCs while the mitochondrial mass in 3D cultured MSCs was low initially. When mitochondria were segregated into punctuate, rods and networks, a cultivation-induced increase in punctuate and network mitochondria was observed in 2D cultured MSCs of passage 3. Finally, mRNA and protein expression of the immunomodulatory molecule IDO relied on stimulation of 2D culture MSCs with pro-inflammatory cytokines IFN-γ and TNF-α with no effect upon HPL supplementation. GARP mRNA and surface expression was constitutively expressed and did not respond to HPL supplementation or stimulation with IFN-γ and TNF-α. In conclusion, we can say that MSCs cultivated in 2D and 3D are sensitive to medium supplementation with HPL with changes in actin filament formation, mitochondrial dynamics and membrane elasticity that can have an impact on the immunomodulatory function of MSCs.